Analisis Level Kognitif Soal Trigonometri Buku Teks Matematika SMA/MA Kelas X Berdasarkan Taksonomi Bloom Revisi - Rahma Nia Juita; Hari Sumardi; Hanifah Hanifah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
The Mathematics Textbook for 10th grade of senior high school published by the Ministry of Education and Culture is the main book used in learning at school. However, there are teachers who rarely use the problems in the book when giving exercises to students, especially on Trigonometry. Whereas, the distribution of cognitive levels on the competency test in the book is not known. This study was aimed to describe the distribution of cognitive levels of Trigonometry’s competency test questions in mathematics book for 10th grade published by the Ministry of Education and Culture based on the revised Bloom's Taxonomy. This type of research was descriptive research with documentation method. The instruments that used in this study were cognitive level classification sheet and cognitive level conformity validation sheet. The results showed that from 171 questions there was a question that was incomplete and as many as 170 questions that deserved to be analyzed obtained a distribution of cognitive level remembering (C1) as 5 questions , understanding (C2) as 44 questions , applying (C3) as 99 questions , analyzing (C4) as 15 questions , and evaluating (C5) as 7 questions , and it did not contain the cognitive level of creating (C6).